Understanding the Implementation of Telerehabilitation at Pre-Implementation Stage: A Systematic Literature Review - Jafni T.I.; Bahari M.; Radman A.; Waidah Ismail (Elsevier B.V., 2024)
Indexed by WOS/Scopus/ERA